1996
DOI: 10.1002/art.1780390914
|View full text |Cite
|
Sign up to set email alerts
|

Chondroprotective effect of intraarticular injections of interleukin‐1 receptor antagonist in experimental osteoarthritis. Suppression of collagenase‐1 expression

Abstract: Objective. To investigate the in vivo effect of recombinant human interleukin-1 receptor antagonist (rHuIL-1Ra) on the development of lesions and the expression of metalloproteases in the canine experimental osteoarthritis (OA) model.Methods. The right anterior cruciate ligament was sectioned percutaneously in 3 groups of dogs. The control group (n = 5) received an intraarticular injection of sterile physiologic saline (1 ml) twice weekly for 4 weeks starting on the day of surgery. The remaining 2 groups recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
181
1
7

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 336 publications
(202 citation statements)
references
References 34 publications
(21 reference statements)
13
181
1
7
Order By: Relevance
“…It is important to note that we have already observed similar differences when testing the effects of other drugs in this model (20,21,26,27). Although the exact reason for these differences remains unknown, it is likely that the effectiveness of the drugs on the different pathophysiologic mechanisms of OA may vary between the condyles and the plateaus.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It is important to note that we have already observed similar differences when testing the effects of other drugs in this model (20,21,26,27). Although the exact reason for these differences remains unknown, it is likely that the effectiveness of the drugs on the different pathophysiologic mechanisms of OA may vary between the condyles and the plateaus.…”
Section: Discussionsupporting
confidence: 53%
“…At this time, it is not known whether the data obtained from animal model experimentation can be extrapolated to clinical observations. The experimental dog model of ACLT-induced OA has been used extensively for such purposes (20,21,23,(25)(26)(27) and could thus be an exception and serve as a useful tool in the study of human OA. Studies have recently shown that the positive effects of doxycycline on OA structural changes in an experimental dog model of OA (28) could also be seen in patients with knee OA treated with this drug (29).…”
Section: Discussionmentioning
confidence: 99%
“…Intraarticular expression has also been confirmed after ex vivo transfer of the IL1Ra gene [2], and for several weeks following in vivo delivery of the adenoviral IL-1 Ra construct [l 11. In vivo, IL-I Ra has been shown to preserve articular cartilage, having beneficial effects on the histology of the synovial membrane, along with decreased pain and generalized joint disease [5,11,17,29].…”
Section: J L Huupr Et Ul I Jiiioumul Q F Ortlzopuedic Reseurcli 23mentioning
confidence: 99%
“…Local delivery of IL-1Ra into the joint space has been evaluated in a canine model of OA, with twice weekly intraarticular injections of 2 mg or 4 mg of protein being found to be chondroprotective (14). The safety of intraarticular IL-1Ra delivery has also been demonstrated in human clinical trials using single injections of 150 mg (15).…”
mentioning
confidence: 99%